Organoselenium Compounds in Catalysis - Gallo, Carola (2023)
In this article we have focused on the use of selenium in catalysis along with the proposed reaction mechanisms. With the increasing interest in selenium chemistry, we have attempted to highlight the most significant features on this subject, mainly in the last years. Selenium-containing catalysts have a key role in many transformations; for example, those oxidation reactions that should be performed under very mild and controlled conditions. In addition, the weak selenium-oxygen bonding interaction proved to be very useful as a catalytic approach for specific transformations. The catalytic cycles of each appropriate transformation are fully reviewed.